Optimasi Sistem MagnetoHydrodynamics (MHD) Sederhana untuk Aplikasi Aliran Fluida - Hawinda Restu Putri; Bekti Afre Ratri; Nining Kusumastuti; Siti Nurul Khotimah (Postgraduate, University of Mataram, 2025)
Magnetohydrodynamics (MHD) studies the relationship between electromagnetism and fluid mechanics, a concept with various practical applications, including marine propulsion systems and electromagnetic pumps. This study aims to optimize a simple MHD system to improve the performance of fluid rate measurement based on electromagnetic principles. Optimization is carried out through the analysis of the influence of variations in several system characteristics, namely the given electrical voltage, the distance between electrodes, the length of the electrode, and the salinity of the saltwater. The method employed is experimental, utilizing a simple MHD system design that enables the quantitative observation of changes in the speed of saltwater resulting from the interaction between magnetic and electric fields. The speed of saltwater is measured using a visual approach with the Tracker analysis application. The results showed that increasing the voltage and salinity of the saltwater, as well as decreasing the electrode length or the distance between electrodes, all contribute to increasing the speed of saltwater flow. In other words, each parameter makes a significant contribution to fluid dynamics, thereby allowing for the optimal configuration of the MHD system. The findings in this study are expected to serve as the basis for the development of simple MHD-based fluid rate measurement instruments that are efficient and applicable, enabling a concrete illustration of electromagnetic theory and fluid dynamics.